Pilot-Testing of “Healthy Body Healthy Mind”: An Integrative Lifestyle Program for Patients With a Mental Illness and Co-morbid Metabolic Syndrome - Murphy, Jenifer A.; Oliver, Georgina; Ng, Chee H.; Wain, Clinton; Magennis, Jennifer; Opie, Rachelle S.; Bannatyne, Amy; Sarris, Jerome (Frontiers in Psychiatry, 2019)
Background: Metabolic syndrome and co-morbid physical health conditions are highly prevalent in people with a mental illness. Modifiable lifestyle factors have been targeted to improve health outcomes. Healthy Body Healthy Mind (HBHM) program was developed to provide an integrated evidence-based program incorporating practical diet and exercise instruction; alongside meditation and mindfulness strategies, and comprehensive psychoeducation, to improve the physical and mental health of those with a mental illness. Methods: We report on two data points: (1) Qualitative data derived from the first HBHM program (version 1) exploring its utility and acceptance according to patient feedback; (2) Biometric and mental health data collected on the modified and enhanced 12-week HBHM program (version 2) involving a pilot of 10 participants. Mental and physical health outcomes, weight, abdominal circumference, fasting glucose, cholesterol, and triglycerides were measured at program entry and completion. Results: Qualitative data from HBHM version 1 provided valuable feedback to redevelop and enhance the program. At the end of the HBHM (version 2) 12-week program, a significant mean weight loss of 2 kg was achieved, p = 0.023. There was also a significant reduction in abdominal circumference (mean = 2.55 cm) and a decrease in BMI of almost one point (mean = 0.96 kg/m2), p = 0.046 and p = 0.019, respectively. There were no significant changes in mental health measures or on any other biometrics. Conclusion: Pilot data from the HBHM program found significant reductions in weight and abdominal obesity. The HBHM program could benefit from further modifications, and study replication is required using a controlled design in a larger sample.